2014
DOI: 10.1179/1476830513y.0000000106
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 supplementation ameliorates inflammatory markers in patients with multiple sclerosis: a double blind, placebo, controlled randomized clinical trial

Abstract: CoQ10 supplementation at a dosage of 500 mg appears to decrease the inflammatory markers (TNF-α, IL-6, and MMP-9) in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 42 publications
5
80
0
Order By: Relevance
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 89%
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 89%
“…Lee et al found that 12 weeks of CoQ10 supplementation at a dosage of 300 mg/day significantly reduced serum levels of TNF-a in patients with coronary artery disease [26]. In another study, Sanoobar et al showed the significant effect of oral CoQ10 supplementation (500 mg/day) on IL-6 and TNF-a in patients with multiple sclerosis [28]. In contrast to our study, a 200 mg/day dose of CoQ10 for 8 weeks had no effect on hs-CRP levels in patients with diabetes [16].…”
Section: Discussionmentioning
confidence: 96%
“…The endogenous production of coenzyme Q10 declines after the age of 20, and at the age of 80, only half of endogenous production can be found in the heart [40]. Substantial efforts have been done in numerous studies where supplementation of coenzyme Q10 has been evaluated in different conditions, like multiple sclerosis [41,42] , in Parkinson´s disease [43], in patients with renal injury treated with shockwave lithotripsy [44], in male infertility [45], and in heart disease but with inconsistent results [46][47][48]. Fotino et al reported in a meta-analysis consisting of 13 studies and 395 patients increased cardiac function after coenzyme Q10 supplementation even if the total study sample was small [49].…”
Section: Coenzyme Q10mentioning
confidence: 99%